FACTORS ASSOCIATED WITH CERVICAL CANCER SCREENING BEHAVIOUR OF WOMEN ATTENDING GYNAECOLOGICAL CLINICS IN KAZAKHSTAN: A CROSS-SECTIONAL STUDY - Issa, Torgyn; Babi, Aisha; Azizan, Azliyati; Alibekova, Raushan; Khan, Saleem A.; Issanov, Alpamys; Chan, Chee Kai; Aimagambetova, Gulzhanat (SAGE Publications, 2021)
Objective: Although cervical cancer could be prevented through medical screening, it remains one of the top causes of cancer-related morbidity and mortality all over the world. A number of factors may contribute to cervical cancer screening behaviour of women. The aim of this study was to investigate factors related to cervical cancer screening behaviour of women in Kazakhstan. Methods: This was a cross-sectional survey-based study with a total of 1189 participants. Women attending gynaecological clinics aged between 18 and 70 years were administered paper-based questionnaires about their awareness of cervical cancer, the associated risk factors, and cervical cancer screening. Student t test or Wilcoxon rank-sum test and chi-square test or Fisher’s exact test, where appropriate, were used to determine associations with categorical independent variables. Results: The mean age of participants was 36.5 ± 10.1 years. Less than half (45.7%) of the participants had been screened for cervical cancer. The key factors related to the cervical cancer screening behaviour of women in this study included age, having a larger number of children, regular menstrual function, awareness of Pap smear test, and free screening programme for cervical cancer, and the causal association of human papillomavirus with cervical cancer. Conclusion: This study revealed several significant factors predicting screening behaviour in Kazakhstani women. To improve the rate of screening, there is a need to increase public knowledge and awareness of cervical cancer and opportunities for the free screening programme in the female population of Kazakhstan. Keywords: cervical cancer, human papillomavirus, Kazakhstan, screening, screening behaviour
Keywords: cervical cancer; human papillomavirus; Kazakhstan; screening; screening behaviour; Type of access: Open Access